Miocardiopatia não compactada: um relato de caso em atleta de alto rendimento - GERMANOVIX, Jéssica Berteloni (2021)
Noncompaction cardiomyopathy (NCM) is characterized by the presence of abnormal trabeculations in the left ventricle (LV), most commonly in the apex, which may be associated with LV dilation or hypertrophy, or other congenital heart diseases. Objective: Describe the clinical and diagnosis of non-compaction cardiomyopathy, as well as the treatment and prognosis of the patient. Case report: M.L.S, female, swimming athlete, 100 and 200m crawl and back tests, in 2010, at 16 years of age, in outpatient care for suspected cyst in the right wrist, a possible arrhythmia was questioned on physical examination. The requested electrocardiogram (ECG) was normal, however, magnetic resonance imaging (MRI) and echocardiogram showed elevated trabeculations in the middle and apical portion of the left ventricular (LV) lateral wall, with relation between the non-compacted myocardium on the compacted myocardium was 2,7, diagnosed with non-compacted cardiomyopathy (MNC). Even asymptomatic, acetylsalicylic acid (ASA) and interruption of sports competitions were recommended. Discussion: MNC is considered a rare and congenital heart disease, due to non-compression of the myocardium, possibly between the fifth and eighth embryonic weeks. MNC can be found in 3% of patients with reduced ejection fraction and heart failure, and in up to 8% of athletes. Conclusion: More scientific studies on MNC are needed in asymptomatic patients, such as the patient studied, as a way to contribute to a better understanding of the management of athlete patients and the possible evolution to a symptomatic picture with possible complications.